ECG Signal Compression Based on Wavelet Packet Transform and Residual Vector Quantization - Beki?Ryazici, Tahir; Aydemir, Gürkan; Gürkan, Hakan (Institute of Electrical and Electronics Engineers Inc., 2025)
Efficient compression of electrocardiogram (ECG) signals is of great importance, particularly in facilitating data transmission and reducing storage costs in remote monitoring systems. For this purpose, a two-stage compression method based on Wavelet Packet Transform (WPT) and Residual Vector Quantization (RVQ) has been developed. The performance of the proposed method was tested on the widely used MIT-BIH Arrhythmia dataset. Performance evaluation was conducted using statistical metrics such as compression ratio (CR), percentage root-mean-square difference normalized (PRDN), and quality score (QS). Experimental results show that the method achieved a compression ratio of 8.8 : 1 with 6.54% PRDN and 17.6 : 1 with 14.38% PRDN. © 2025 IEEE.
Dalgacik Paket D n s m ve Artik Vekt r Nicemlemesine Dayali EKG Sinyal Siki stirmasi
33rd IEEE Conference on Signal Processing and Communications Applications, SIU 2025 -- 2025-06-25 through 2025-06-28 -- Istanbul -- 211450
Keywords: ECG signals; Residual vector quantization; Signal compression; Wavelet packet transform